Dishonesty Concessions in Teams: Theory and Experimental Insights from Local Politicians in India - Arnab K. Basu; Nancy H. Chau; Anustup Kundu; Kunal Sen (Institute of Labor Economics (IZA), 2025)
Economic theory predicts that dishonesty thrives in secrecy. Yet, team-based decisions are ubiquitous in public policy-making. How does teamwork influence the tendency for selfdealings when public servants – both honest and corrupt – must work together to make decisions under the veil of within-group secrecy? This paper designs a field experiment guided by a theoretical model of team-level dishonesty, where we define and unpack the drivers of the dishonesty concessions that individuals make in a team-setting as a cooperative bargain between team players. The experiment is implemented in a sample of village council (Gram Panchayat) members in the State of West Bengal in India, extending the die roll experiment à la Fischbacher and Föllmi-Heusi (2013). By bringing together evidence pointing to the distinctive contributions of peer dishonesty influence, social image concerns (e.g as a gender- and seniority-based marker), and power asymmetry effects (e.g. between politicians in reserved and openly contested seats) in guiding the dishonesty concessions individuals choose to make in a team, our findings shed light on the salience and nuanced role of committee composition in teams of public officials.
Keywords: D9; O12; K42; 330; politician dishonesty; peer effects; social image; power asymmetry